Membongkar Antroposentrisme Hukum Indonesia dalam Perspektif Aktor-Jaringan dan Struktur Sosial pada Fenomena Krisis Lingkungan - Rofiki; Dini Rahmawati; Ahmad Fatkhur Rohman (Yayasan Ekologi Masyarakat dan Sains, 2025)
The global environmental crisis demands a deconstruction of the legal paradigm that is still dominated by anthropocentrism, a view that places humans at the center of all norms and interests. Using a qualitative approach with a library study design, this article explores the thoughts of Bruno Latour and Murray Bookchin as two philosophers who offer alternative approaches to the relationship between humans, law, and nature. Through Latour's perspective, law is understood as a network of actors, including non-human actors (nature), who have agency in political and legal processes. Meanwhile, Bookchin emphasizes the importance of social ecology and critiques hierarchical domination as the root of the ecological crisis. This article is a critical philosophical study with descriptive and reflective content analysis. This research shows that current ecological inequality is a highly dominant and hierarchical social structure. Actors in the formulation of law or policy are often limited, and the broader community is not widely involved in the policy-making process. This article is expected to encourage the reformulation of environmental law that is more inclusive of the entire network of actors in responding to contemporary ecological challenges—including the moral crisis within them.